2015
DOI: 10.1111/jhn.12306
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal growth and health outcomes in nutritionally at‐risk children who received long‐term nutritional intervention

Abstract: Background: The benefits of short-term oral nutritional supplementation (ONS) in undernourished children are well-established. The benefits of long-term ONS in promoting longitudinal growth and health in children who are at risk of undernutrition have not been reported previously. Methods: In this 48-week prospective, single-arm, multicentre trial, 200 Filipino children aged 3-4 years with weight-for-height percentiles from 5th to 25th (WHO Child Growth Standards) were enrolled. Parents received dietary counse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 28 publications
2
42
1
4
Order By: Relevance
“…One example involves a FUF-YC product specifically marketed as “Nutrition to help kids grow” [78] and presently advertising its significance as a “2 per day” snack, helping “kids ages 3–4 grow out of at-risk weight-for-height percentiles” as it “helps kids gain weight in just 8 weeks” [79]. The corporate-sponsored study cited as the evidentiary base is an intervention with no control arm, involving 199 Filipino children with baseline mean age of 41 months (range, 3 months to 48 months), weight-for-height of 14.8 and 17th percentiles (female, male), and daily intake of 1379 kcal [80]. The authors define individuals between the 2.3 and <25th percentile in weight-for-height as at-risk of wasting.…”
Section: Feeding Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…One example involves a FUF-YC product specifically marketed as “Nutrition to help kids grow” [78] and presently advertising its significance as a “2 per day” snack, helping “kids ages 3–4 grow out of at-risk weight-for-height percentiles” as it “helps kids gain weight in just 8 weeks” [79]. The corporate-sponsored study cited as the evidentiary base is an intervention with no control arm, involving 199 Filipino children with baseline mean age of 41 months (range, 3 months to 48 months), weight-for-height of 14.8 and 17th percentiles (female, male), and daily intake of 1379 kcal [80]. The authors define individuals between the 2.3 and <25th percentile in weight-for-height as at-risk of wasting.…”
Section: Feeding Obesitymentioning
confidence: 99%
“…This “improvement” was a mean increase of 3.5 cm in height (a 0.12 Z-score change) by week 24 (accrued as 0.5, 0.7, 1.2, and 1.1 cm sequential increments at 4, 8, 16, and 24 weeks) and a weight-for-height Z-score (WHZ) change of 0.46 by week eight. The authors conclude that these results show a catch-up growth phase in weight followed by a maintenance growth phase of height gain, a successful “preventive approach of targeting children at risk of undernutrition” with “significant benefits on growth” and “low risk of excessive weight gain” as the WHZ change was below 0.67 [80]. …”
Section: Feeding Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, treatment of stunted children with ONS for 6 months significantly improved HAZ by 0.25 units, WHZ by 0.72 units, and WAZ by 0.65 units from baseline. Other studies have also shown significant improvements in linear and ponderal growth in non-stunted children after intervention with ONS [34,35]. However, in some studies that used similar ONS in non-stunted children, there was no significant improvement in HAZ after ONS application, although there was a trend towards the improved height and HAZ in the intervention groups [39,40].…”
Section: Discussionmentioning
confidence: 96%
“…ONS also significantly reduced the incidence of upper respiratory tract infections in these children [34]. Additionally, long-term intervention with ONS plus initial DC promoted longitudinal ponderal and linear growth in nutritionally-at risk children aged 36-48 months [35]. Long-term ONS with initial DC was also associated with improved dietary diversity as well as adequate dietary intake of nutrients over 48 weeks and did not interfere with the intake of family foods [36].…”
Section: Introductionmentioning
confidence: 99%